PENGGUNAAN MEDIA RODA BACA PUTAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA AWAL SISWA KELAS 1 SDN BATUPUTIH LAOK II - Dandy Kurniawan; Trio Wahyudi; Siti Subaida; Hemayatul Kubro; Zakiyah Zakiyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This research is motivated by the low level of early reading skills among several first-grade students at SDN Batuputih Laok II, where students still face difficulties in recognizing alphabet letters, frequently switch them, and some do not recognize letters at all. The purpose of this study is to describe the use of the "Roda Baca Putar" (Spinning Reading Wheel) media in improving the early reading skills of first-grade students. The research method used is descriptive qualitative. The results indicate that the use of the spinning reading wheel media provides a significant positive impact. Through the activities of spinning the wheel and arranging letters, students become more active, enthusiastic, and do not feel bored during the learning process. Improvements in ability are evident in the students' success in recognizing the alphabet and their emerging ability to combine letters into syllables and simple words. The conclusion of this study is that the spinning reading wheel media is an effective solution for creating a conducive learning atmosphere and increasing the basic literacy skills of lower-grade students.